PERAN PERCEIVED QUALITY MEMEDIASI PERCEIVED PRICE TERHADAP PERCEIVED VALUE PENGGUNA JASA LAYANAN RUMAH KOS JIMBARAN - Buditama, Satya Pariana; Aksari, Asti (E-Jurnal Manajemen, 2017)
Consumer’s perceived value differs among individuals. As marketers, consumer perceived value must be understood as it represents consumer behavior before purchase, during purchase and after purchase. This research was conducted to examine the relationship among consumers’ perceived price, perceived quality and perceived value of boarding houses in Jimbaran. Purposive sampling method was used to collect data with a total sample of 100 respondents and path analysis was used to analyse the data. The result of this study shows that perceived price has a positive and significant effect on perceived quality but insignificant effect on perceived value, while perceived quality has a positive and significant effect on perceived value and it also significantly mediates the relationship between perceived price and perceived value. This indicates that providers of boarding houses in Jimbaran should set their prices that reflects the quality of their rooms and services.
Keywords: perceived price, perceived quality, perceived value, boarding houses.